Analisis Perlakuan Pajak Pertambahan Nilai (PPN) atas Jasa Outsourcing Berdasarkan Management Fee dan Total Tagihan - Intan Paujijah; Riyandi Nur Sumawidjaja; Yoyo Sudaryo (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
This study analyzes the treatment of Value Added Tax (VAT) on security outsourcing services provided by PT Karya Cahaya Anue by comparing the tax base (DPP) calculated from the management fee versus the total invoice value. Outsourcing service billing typically consists of two cost groups: labor-related costs (salary, BPJS, THR, uniforms, and operational costs) and the management fee received as compensation for managerial services. In practice, some service users request that VAT be calculated on the total invoice, while Minister of Finance Regulation (PMK) Number 83/PMK.03/2012 stipulates that when labor costs are clearly itemized separately from the service fee in the tax invoice, the VAT base should use the "Other Value," represented by the management fee. This research uses a qualitative case study method, analyzing cooperation agreements, cost breakdowns, tax invoices, and procurement documents. The results show that VAT calculated on the management fee for a 26-personnel contract amounted to Rp1,554,818.76, while VAT calculated on the total invoice of Rp155,481,875.57 amounted to Rp17,103,006.31, a difference of Rp15,548,187.55, roughly eleven times higher. Transactions in which the company consistently separates labor costs from the management fee in the contract, cost breakdown, and tax invoice comply with PMK Number 83/PMK.03/2012, whereas transactions using total billing at the client's request do not fully comply. The company is advised to standardize its VAT base policy using the management fee to avoid fiscal correction risk and to prevent over-collection of VAT from service users.